Literacy practices and constructions among migrant Muslim Filipino families - Bumanglag, Carolyn A. (Education Quarterly, 2011)
This ethnographic study examined literacy practices and their meanings among migrant Muslim Filipino families. Data collection involved participant observation, semi-structured interviews, and collection of texts and artifacts related to reading in homes for a period of three months. Participants for this study were three Maranao families who lived at the Islamic Center and migrated from Lanao del Sur.